Service-learning experiences for pre-service teachers: cultural competency and behavior management challenges when working with a diverse low-income community. (4th July 2022) - Daum, David N.; Marttinen, Risto; Banville, Dominique
ABSTRACT: Background: Service-learning is an approach in teacher education to expose pre-service teachers (PSTs) to experiences they will encounter when they enter the profession. During these service-learning experiences, PSTs experience issues related to behavior. K-12 students are increasingly diverse, and teachers and schools must adapt to meet their needs. Purpose: This study examined how PSTs described issues related to behavior management and issues of culture when participating in a service-learning program in a low-income community. Methods: This study employed a case study approach to investigate PST's experiences conducting an afterschool program in a diverse low-socioeconomic area. Nine PSTs delivered the REACH program at an elementary school and met twice per week for two hours each day over the academic year. Session activities related to literacy development, fitness, nutrition, and character development. The REACH approach was grounded in Teaching Personal and Social Responsibility (Hellison 2003. "Teaching Personal and Social Responsibility in Physical Education." In Student Learning in Physical Education: Applying Research to Enhance Instruction, edited by S. J. Silverman, and C. D. Ennis, 241–254. Champaign, IL: Human Kinetics) and Positive Youth Development (Holt et al. 2017. "A Grounded Theory of Positive Youth Development Through Sport Based on Results from a Qualitative Meta-Study." International Review of Sport and Exercise Psychology 10: 1–49). Data were collected via journals and semi-structured interviews. Open and axial coding techniques were used for data analysis. Social Cognitive Theory (Bandura 1986. Social Foundations of Thought and Action: A Social Cognitive Theory . Englewood Cliffs, NJ: Prentice-Hall) was used as a theoretical framework. Findings: Two main themes emerged; the first relates to how PSTs navigated issues of behavior management. Specifically, the problems that PSTs had navigating off-task behaviors, learning through trial and error, and what students do and say are not always rational to adults. The second main theme describes how PSTs negotiated working at a low-income school. This theme includes insight into PSTs' personal growth as well as how they navigated issues of cultural competence. Discussion: PSTs conveyed many issues including gaining and maintaining student attention, participation levels, and dealing with off-task behaviors. Even though the PSTs had learned positive behavior management techniques, they used exercise as punishment because students asked for it. Listening to students helped PSTs in understanding their students' needs and how they perceive their environment. Additionally, cultural biases, similarities, and differences between PSTs and the students were discussed and how that might have impacted the learning environment. Language, specifically not being able to speak Spanish, was a barrier but did not affect PSTs' ability to develop relationships with their students. Conclusions: This study provides a greater understanding of the social dynamic between service providers and recipients during service-learning opportunities. Findings indicate that additional attention needs to be afforded to the development of behavior management skills in PSTs. This includes providing structured hands-on experiences for PSTs to navigate alternate behavior management strategies. Lastly, PSTs should be purposely exposed to teaching children from cultures and experiences different than their own, to help develop culturally responsible teachers.